2018
DOI: 10.1167/iovs.18-24462
|View full text |Cite
|
Sign up to set email alerts
|

Regional Deformation of the Optic Nerve Head and Peripapillary Sclera During IOP Elevation

Abstract: PurposeTo measure the deformation of the porcine optic nerve head (ONH) and peripapillary sclera (PPS) in response to intraocular pressure (IOP) elevation.MethodsHigh-frequency ultrasound was used to image the ONH and PPS of 12 porcine eyes during ex vivo inflation testing from 5 to 30 mm Hg. A speckle tracking algorithm was used to compute tissue displacements in the anterior-posterior direction and expansion of the scleral canal. Through-thickness, in-plane, and shear strains were calculated within the ONH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…How these IOP fluctuations can contribute to the onset and progression of glaucoma is not completely understood. It is believed that the IOP increase could directly damage the optic nerve but also this elevation could affect the blood flow indirectly harming the optic nerve [34][35][36]. Finally, it has been described that astrocytes in the optic nerve head are mechanosensitive and can respond to the mechanical stress induced by IOP increase, reducing the trophic support or changes in extracellular remodeling in the optic nerve [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…How these IOP fluctuations can contribute to the onset and progression of glaucoma is not completely understood. It is believed that the IOP increase could directly damage the optic nerve but also this elevation could affect the blood flow indirectly harming the optic nerve [34][35][36]. Finally, it has been described that astrocytes in the optic nerve head are mechanosensitive and can respond to the mechanical stress induced by IOP increase, reducing the trophic support or changes in extracellular remodeling in the optic nerve [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…7 In a clinical study on optic nerve head changes during an acute IOP rise, we observed a thinning mainly of the prelaminar tissue, while the lamina cribrosa showed morphological changes mostly with an IOP elevation by >15 mm Hg. 9 Applying sonography, Pavlatos et al 20 found that a posterior displacement of the sclera and optic nerve head was associated with the IOP in a non-linear manner. The current study suggested that the IOP rise-associated displacement in the lamina cribrosa may occur in the anterior-posterior direction (ie, thinning of the prelaminar tissue and backward bowing of the lamina cribrosa) and in the frontal plane leading to a lateral movement of the LCPs.…”
Section: Figurementioning
confidence: 99%
“…9 There are several experimental techniques currently being used to investigate changes in the mechanical compliance of the ONH and posterior scleral surface. 10,11 Most of these identify the pressure-induced deformation at the level of the LC and use this information to determine the biomechanical properties of the tissue. 10 However, it is known that the ONH and anterior laminar surfaces are not only displaced posteriorly but also anteriorly (with reference to Bruch's membrane opening) in a significant portion of glaucoma patients.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Most of these identify the pressure-induced deformation at the level of the LC and use this information to determine the biomechanical properties of the tissue. 10 However, it is known that the ONH and anterior laminar surfaces are not only displaced posteriorly but also anteriorly (with reference to Bruch's membrane opening) in a significant portion of glaucoma patients. 12 Characterizing elasticity of the ONH over physiological pressures may provide a better understanding of how changes in IOP lead to changes in the mechanical environment of the ONH.…”
Section: Introductionmentioning
confidence: 99%